Efektivitas Penggunaan Poli Aluminium Klorida (PAC) dan Aluminium Sulfat (Tawas) Dalam Pengolahan Limbah Cair Industri pada Waste Water Treatment Plant (WWTP) PT. KIMA Makassar dengan Metode Koagulasi Menggunakan Jar Test - Harun Pampang; Maria Assumpta Nogo Ole; Zakiyah Darajat (Universitas Pahlawan Tuanku Tambusai, 2022)
Wastewater in industrial areas has various contents. The levels of pollutant substances in waste water have been regulated in industrial area waste water quality standards stipulated in Government Regulations. One method used to achieve quality standards is a chemical process, namely adding chemicals as coagulants using a jar-test machine. In this study, the coagulation process of liquid waste from PT. Makassar Industrial Area with the addition of polyaluminium chloride (PAC) and aluminum sulfate (alum) which aims to study the effectiveness of using two types of coagulants with variations of 0.02, 0.04, 0.06, and 0.08 grams in 500mL of wastewater. After 1 minute fast stirring and 10 minutes slow stirring then leaving for 10 minutes, the TSS test showed that the addition of alum was able to reduce TSS better than the addition of PAC. The addition of 0.04 grams of alum resulted in an effectiveness of 91.71%, while for PAC the best results were the addition of 0.06 grams of coagulant with an effectiveness of 46.13%. Keywords: coagulation, jar-test, alum, PAC, wastewater treatment